Optimization of District Metered Areas for Reducing Non-Revenue Water - Swantara, Dewa Made Indra Widnyana; Razif, Mohammad; Pramitasari, Yantri Novia (Universitas Diponegoro, 2025)
Non-revenue water (NRW) is a significant issue for water supply in Indonesia, with a national NRW rate of 33.7% in 2022 and even higher at PT Air Minum Giri Menang (PT AMGM) at 36.21%. Although District Metered Areas (DMA) were implemented in 2018, their effectiveness has been limited due to poor monitoring. This study evaluates the current DMA conditions by creating a water balance and using EPANET 2.2 software for analysis, along with formulating optimization strategies through technical, financial, and institutional assessments. The research identifies fifteen DMAs, with five being well-established. Two DMAs were chosen for optimization. Simulations showed that many pipes in these DMAs did not meet flow speed standards. Water pressure in DMA Graha Permata Kota was fully satisfied at 100%, while DMA Elit Kota Mataram achieved 84.5%. The study noted a significant NRW reduction by an average of 27.26% in the selected DMAs. The total repair cost was Rp 14,725,300, leading to additional annual revenue of Rp 128,747,424 and a positive feasibility analysis. Institutional performance was rated as